9-[(2,6-Dimethoxyphenoxy)carbonyl]-10-methylacridinium trifluoromethanesulfonate - Krzymiński, Karol (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(23)H(20)NO(4) (+)·CF(3)SO(3) (−), the cations are linked through C—H⋯O, C—H⋯π and π–π interactions [centroid-centroid distances = 3.641 (2) and 3.885 (2) Å]. The cation and the anion are held together by C—H⋯O and S—O⋯π interactions. The acridine ring system and the benzene ring in the cation are oriented at a dihedral angle of 8.7 (1)°. The carboxy group is twisted at an angle of 83.2 (1)° relative to the acridine skeleton.